Genome-Wide Identification and Transferability of Microsatellite Markers between Palmae Species - Xiao, Yong; Xia, Wei; Ma, Jianwei; Mason, Annaliese S.; Fan, Haikuo; Shi, Peng; Lei, Xintao; Ma, Zilong; Peng, Ming (Frontiers in Plant Science, 2016)
The Palmae family contains 202 genera and approximately 2800 species. Except for Elaeis guineensis and Phoenix dactylifera, almost no genetic and genomic information is available for Palmae species. Therefore, this is an obstacle to the conservation and genetic assessment of Palmae species, especially those that are currently endangered. The study was performed to develop a large number of microsatellite markers which can be used for genetic analysis in different Palmae species. Based on the assembled genome of Elaeis guineensis and Phoenix dactylifera, a total of 814 383 and 371 629 microsatellites were identified. Among these microsatellites identified in Elaeis guineensis, 734 509 primer pairs could be designed from the flanking sequences of these microsatellites. The majority (618 762) of these designed primer pairs had in silico products in the genome of Elaeis guineensis. These 618 762 primer pairs were subsequently used to in silico amplify the genome of Phoenix dactylifera. A total of 7 265 conserved microsatellites were identified between Elaeis guineensis and Phoenix dactylifera. One hundred and thirty-five primer pairs flanking the conserved SSRs were stochastically selected and validated to have high cross-genera transferability, varying from 16.7% to 93.3% with an average of 73.7%. These genome-wide conserved microsatellite markers will provide a useful tool for genetic assessment and conservation of different Palmae species in the future.